Analysis of Prioritization of Road Development in Regional Development in North Labuhanbatu Regency - Barus, Ester Maria; Lindarto, Dwi; Sulistiyono, Nurdin (Budapest International Research and Critics University, 2021)
The purpose of this study is to find out how effective location / area conditions are a top priority for the determination of road construction in North Labuhanbatu Regency. The interview data showed that 3 (three) criteria taken in this study, using the Analytical Hierarchy Process (AHP) method were obtained, namely, the cost of development (33.7%), road conditions (46.9%) is the most dominant criterion and level of importance (19.4%). By including 3 (three) criteria against 15 (fifteen) proposals, the evaluation of the comparison of road development priorities of North Labuhanbatu Regency in Fiscal Year 2019 with the priority of alternative road development in regional development obtained 2 (two) road activities that became priorities for Alternative Road Development, namely Hardening Jl Pasar Barat Towards Block I Lingk. West Market Kel. Tanjung Leidong Kec. Kualuh Leidong and Jl Bawal Lingk Development. Kp Baru 4 Kel. Tanjung Leidong Kec. Kualuh Leidong.